Genealogia e spin-offs empreendedoras num cluster industrial de malharias no Brasil - Paula, Roberta Manfron de (2015)
The main goal of this thesis was to understand the entrepreneur spin-offs phenomenon ??? that is, the new companies settled up by workers that drop of the companies where they worked previously in order to build up their own companies ??? as a start up to understand the impact of the genealogic effects in regional dynamics. This research describes a single scenario that can be very useful in an effort to understand what can cause people reasons to create new companies and so forth, identify the coming up of a cluster. In this direction, some research problems were settled: What is really known about spin-offs and what main books and theories have caused some impact on researches about spin-offs? Is it possible to observe what the genealogy features of a cluster not so sophisticated technologically saying and relatively recent in Brazil are? What are the features, on the settled industries, which are the so called mother companies that contribute to cause entrepreneur spin-offs? In order to do so, I performed three studies with distinct approaches. However, in the context, they explain and complement the goals and the research questions, consolidating the theories, contexts, genealogy and features of the mother firm in bringing up the entrepreneur spin-offs. The first study was about an analysis converging resources to bibliometric techniques and procedures about existing international literature. The sample about this study came up with 812 articles published in international journals. The analysis of citations and co-citations were used and complemented by a factorial analysis, providing a presentation of a structural and longitudinal component of the publications, which made easy to comprehend how the research has evolved among the years. The published studies allowed identifying the main theoretical frames that basis the spin-offs phenomenon, as well as, a group of interest variables to better understand the phenomenon. The second study aimed to identify the existence of entrepreneur spin-offs in a small Brazilian cluster ??? to which I focused on the knitting companies cluster in Monte Si??o. This genealogy study came up with a sample of 232 companies, with data gathered through structured questionnaire. The third study, a statistical empiric one, was supported on data gathered through questionnaire, and came up with a sample of 103 companies. This study aimed to identify a group of features of the settled companies in order to verify which are the mother firms features able to generate new entrepreneur spin-offs. The main results of the three studies show that research on spin-offs phenomenon has evolved over the years to different scenarios, the analysis of cocita????es have highlighted the theoretical ties that consolidate authors in certain research environments. It has been strongly highlighted the academic context favoring the generation of spin-offs through knowledge transfer, innovation and entrepreneurship. It was also identified the way was the seed companies, recognizing six different types of undertakings contained in the cluster, active mothers firms, inactive mothers firms, formal spin-offs, spin-offs of several mothers, informal spin-offs and traditional firms, complementing the results also confirm that it is possible by the attributes of mothers firms generate spin-offs entrepreneurs, thus validating the model.This thesis contributing in causing a global literature perspective about spin-offs, with special emphasis to the Theory of Cost Transaction, Theory of Agency, Resources Based View and its variant Knowledge based View. It also contributes to better understanding the entrepreneur spin-offs and the genealogic effects that provide nuances about the located concentrations of the companies. Presenting the genealogic tree of a cluster can inspire researchers to try to understand the relations among mother-companies and spin-offs to create new companies, so empowering a specific cluster. Finally, it contributes to identify the main factors to generate entrepreneur spin-offs through the attributes of the mother-firms. It is mainly interesting the fact that environments presenting low technologic resources and a small and medium companies dimension can also be prone to entrepreneur dynamics.